Essential and Untrusted. - Ticona, Julia (Dissent (0012-3846))
In the article, the author discusses the issues in the operation of domestic labor platforms in the U.S. like the websites and applications (app) Sittercity and Care.com. These platforms serve as agencies where care workers are hired by families looking for someone to take care of their children. Also mentioned are the author's study of the platforms by conducting interviews with babysitters, nannies, and home-care workers who used them, the alleged discriminatory hiring practices in the platforms, and the need to introduce reforms to resolve the platforms' crucial flaws.